A cyanide-catalyzed imino-Stetter reaction enables the concise total syntheses of rucaparib. Issue 33 (1st August 2022) - Park, Jinjae; Cheon, Cheol-Hong
Abstract : The concise total synthesis of rucaparib was developed from commercially available starting materials using the cyanide-catalyzed imino-Stetter reaction as the key reaction to construct the requisite tetra-substituted indole derivative. Abstract : Two routes toward the synthesis of rucaparib, an FDA-approved drug used for the treatment of ovarian and prostate cancers, have been developed from commercially available starting materials utilizing the cyanide-catalyzed imino-Stetter reaction as the key step for the construction of the indole motif bearing all the desired substituents in their correct positions. In the first-generation synthesis, meta -fluorobenzoate, the starting material currently used in the process chemistry route of rucaparib, was converted into 4, 6-disubstituted 2-aminocinnamic acid derivatives (ester or amide). The cyanide-catalyzed imino-Stetter reaction of aldimines derived from the resulting 2-aminocinnamic acid derivatives and a commercially available aldehyde afforded the desired indole-3-acetic acid derivatives. The final azepinone formation completed the total synthesis of rucaparib in 27% overall yield. To resolve the issues raised in the first-generation synthesis, we further developed a second-generation synthesis of rucaparib. The Heck reaction of a commercially available ortho -iodoaniline derivative with acrylonitrile provided 4, 6-disubstituted 2-aminocinnamonitrile, which was subjected to the imino-Stetter reaction with the same aldehyde to provide the desired indole-3-acetonitrile product. Subsequent construction of the azepinone scaffold completed the total synthesis of rucaparib in 59% overall yield over three separation operations. The synthetic strategy reported herein can provide a highly practical route to access rucaparib from commercially available starting materials (5.2% overall yield in the current process chemistry route vs. 59% overall yield in the second-generation synthesis).